Determination of frequency of Leishmania tropica in laboratory-confirmed cases of cutaneous leishmaniasis using an in-house conventional PCR test - Ur Rashid, Haroon; Naqvi, Sakeenah Hussain; Zafar, Asad; Ikram, Rabiya; Imtiaz, Anam; Sajjad, Rabia (Journal of the Pakistan Medical Association, 2026)
Objective: To develop a low-cost, in-house conventional polymerase chain reaction method for leishmania tropica for epidemiological surveillance of disease. Method: The cross-sectional study was conducted at the Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from October 16, 2023, to April 16, 2024, and comprised biopsy samples received for the diagnosis of cutaneous leishmaniasis. Deoxyribonucleic acid was extracted from the samples and was subjected to real-time polymerase chain reaction for the detection of the leishmania genus on a commercially available detection kit. Positive samples were then run by conventional in-house polymerase chain reaction with primers specific to leishmania tropica targeting covering internal transcribe spacer 2 and 18S <a href="https://www.google.com/search?q=Ribosomal+RNA&oq=what+is+rRNA&gs_lcrp=EgZjaHJvbWUqBwgAEAAYgAQyBwgAEAAYgAQyCwgBEAAYChgLGIAEMgsIAhAAGAoYCxiABDILCAMQABgKGAsYgAQyCwgEEAAYChgLGIAEMgsIBRAAGAoYCxiABDILCAYQABgKGAsYgAQyCwgHEAAYChgLGIAEMgsICBAAGAoYCxiABDILCAkQABgKGAsYgATSAQoyMDgzOGowajE1qAIAsAIA&sourceid=chrome&ie=UTF-8&ved=2ahUKEwi7p5TV5IKSAxXrWUEAHWgDEbUQgK4QegYIAQgAEAU">ribosomal ribonucleic acid region. The in-house conventional polymerase chain reaction was validated by using extracted deoxyribonucleic acid from the promastigote of leishmania tropica as the positive control. The nucleotide sequence was subjected to the basic local alignment search tool, and a phylogenetic tree was constructed on MEGA 5. Results: Of the 73 suspected leishmaniasis cases, 64(87.7%) were from male subjects. Real-time polymerase chain reaction detected leishmania in 33(45.2%) of the samples, which were then assessed by the in-house polymerase chain reaction specific to leishmania tropica and detected 28(84.8%) samples were detected positive (p=0.0003). Sequencing of the internal transcribe spacer 5.8S region and subsequent phylogenetic analysis with 1000 bootstraps showed >95% identity with L.tropica. BLAST analysis showed 96–98% sequence identity (query coverage 98–100%, E-value = 0.0). Conclusions: The development of in-house polymerase chain reaction to test for leishmania tropica was successful in clinical samples, providing a cost-effective alternative to commercially available kits. Key Words: Leishmania, Leishmania tropica, Commercial PCR, In-house PCR. tected positive (p=0.0003). Sequencing of the internal transcribe spacer 5.8S region and subsequent phylogenetic analysis confirmed the genetic identity of the samples. Conclusions: The development of in-house polymerase chain reaction to test for leishmania tropica was successful in clinical samples, providing a cost-effective alternative to commercially available kits. Key Words: Leishmania, Leishmania tropica, Commercial PCR, In-house PCR.